2013
DOI: 10.1108/17590831311306372
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effect of TV advertising appeals on brand attitudes and advertising efforts in Iran

Abstract: PurposeIn recent years, increasing competition in communicational network of Iran has led to attracting more attention to marketing and particularly, advertising activities. The aim of this paper is to examine the effect of TV advertising appeals of communication companies (in this study, MTN Irancell Company) on customers' attitude towards their advertising efforts and their brand.Design/methodology/approachThe aim was achieved through an empirical study involving a survey. Of 400 questionnaires sent out, 384… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 84 publications
3
21
0
3
Order By: Relevance
“…As shown in Table 3, all of the four paths specified in the hypothesised model are found to be statistically significant. When critical ratios are in the range of -1.96 to 1.96, the hypothesis (H 0 ) will be rejected (Asadi et al, 2014;Feiz et al, 2013;Hair et al, 1998).…”
Section: Semmentioning
confidence: 99%
“…As shown in Table 3, all of the four paths specified in the hypothesised model are found to be statistically significant. When critical ratios are in the range of -1.96 to 1.96, the hypothesis (H 0 ) will be rejected (Asadi et al, 2014;Feiz et al, 2013;Hair et al, 1998).…”
Section: Semmentioning
confidence: 99%
“…Two-sided messages work best with an educated audience that tends to make informed choices like industrial buyers. The order in which the views are presented in a two-sided appeal can affect the impact of each message depending upon the audience characteristics (Feiz et al, 2013). Comparative advertising is an advertisement in which a particular product, or service, specifically mentions a competitor by name for the express purpose of showing why the competitor is inferior to the product naming it.…”
Section: Advertising Appealsmentioning
confidence: 99%
“…Comparative advertising, also referred to as 'knocking copy', is loosely defined as advertising where "the advertised brand is explicitly compared with one or more competing brands and the comparison is oblivious to the audience (Feiz et al, 2013).…”
Section: Advertising Appealsmentioning
confidence: 99%
See 1 more Smart Citation
“…opinion seekers. Opinions leaders are interested in particular product fields, make an effort to expose themselves to mass media sources, and are trusted by opinion seekers to provide knowledgeable advice (Walker, 1995;Feiz et al, 2013). Research has found that early adopters (not always, but often opinion leaders) who had satisfactory experience with automobile diagnostic centers led to positive WOM.…”
Section: Introductionmentioning
confidence: 99%